Preparation method and application of acid and alkali resistant high-transmittance black brick polishing glaze

By adjusting the formula of high-thorns dark black throwing glaze, the content of quartz and SIO2 is increased, and the BA-SR system glaze and transparency of pylori are used to solve the with many raw materials such as glaze and transparency. The problem has achieved the effect of strong glazed sensation, improvement of acid and alkalinity, and decreased production costs.

CN119349887APending Publication Date: 2025-01-24GUANGXI MONALISA NEW MATERIALS CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202411742237.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The existing medium and high-permeability deep black glazed brick products have problems such as many pores on the brick surface, poor permeability, poor acid and alkali resistance, and high firing temperature during the production process, resulting in high production costs and poor economic benefits.

Method used

By adjusting the glazed formula, the content of quartz and SiO2 is increased, and the BA-SR system glaze and transparency raw materials are used to optimize the chemical composition of surface glaze and throwing glaze to ensure that the glaze is strong and the acid and alkali resistance are not lower than that GLB grade, which takes into account the stability of the wide -body kiln production and the matching temperature.

Benefits of technology

The black brick surface has strong transparency and improved acid and alkali resistance, which reduces production costs and improves product quality. It is suitable for low-temperature and fast-burning environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119349887A_ABST
    Figure CN119349887A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of acid and alkali resistant high-transmittance black brick polishing glaze, and relates to the technical field of black brick polishing glaze preparation. The black brick polishing glaze comprises the following raw materials in parts by weight: 30-40 parts of potassium feldspar, 3-5 parts of zinc oxide, 5-9 parts of calcined talc, 4-7 parts of wollastonite, 2-6 parts of calcite, 6-9 parts of washed soil, 6-10 parts of barium sulfate, 7-10 parts of strontium sulfate, 7-9 parts of quartz and 6-8 parts of diopside. According to the invention, by adjusting the glaze polishing formula, matching with the existing production cover glaze and overall planning the formula component system, various properties of the glaze are considered, and the stability of the shape of the brick produced by the wide-body kiln and the matching of the firing temperature curve are considered on the premise of ensuring that the glaze of the black brick and the conventional light-color production layout is strong in transparency and the acid and alkali resistance is not lower than the GLB level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of black brick polishing glaze preparation, and in particular to a preparation method and application of acid-alkali resistant and highly transparent black brick polishing glaze. Background Art

[0002] High-transparency deep black polished glazed brick products have unique colors, patterns, and bright colors, so that their decorative effects can fully reflect the sense of magnificence, luxury and nobility. They have always been a rare and excellent product in building materials. With the development of the economy, the application scope of high-transparency deep black polished glazed brick products has been continuously expanded, playing a finishing touch in people's decoration. Due to the limitations of process technology for a long time, the production of high-transparency deep black polished glazed brick products has been difficult to improve the quality and production capacity of the product brick surface, resulting in high production costs, which seriously affects economic benefits and does not meet the purpose of sustainable development strategies. For example, there are many pores on the brick surface, the brick surface has poor transparency, and the acid and alkali resistance does not reach the GLB level. It is urgent to develop a new glaze formula suitable for black bricks, so that the black bricks produced have fewer pores on the brick surface, strong transparency, acid and alkali resistance not lower than the GLB level, and can take into account the production of conventional light-colored products, and can also reduce the situation of changing glazes and switching production, stabilize production, and improve product quality.

[0003] In the prior art, the patent with application number 201811146343.3 discloses a method for preparing acid- and alkali-resistant fully glazed tiles. The patent obtains fully glazed tiles with strong corrosion resistance and good physical properties, but does not involve whether it is suitable for the production of black bricks, and the pores and transparency of black bricks are unknown. The patent with application number 201810604531.X discloses a method for making black gold flower glaze ceramics. The patent uses black base glaze and gold flower glaze to use screen printing. The process is complicated, the firing temperature is high, the cost is high, and the acid and alkali resistance of the brick surface is not involved. The patent with application number 202211607290.7 discloses a glaze and method for surface treatment of black gold flower tiles. The patent provides black gold flower glaze including 92% black gold flower glaze and 8% mineral glaze. The sintering time is 1-2 hours, the cycle is long, the production cost is high, and the acid and alkali resistance of the brick surface is not involved. The patent with application number 202110571680.2 discloses a lava black brick glaze and its preparation method and application. The patent solves the problem of high porosity of black bricks, but the preparation of the black brick glaze requires three ball millings, the process is complicated, and the sintering temperature is high (1160℃-1250℃) when used to make black bricks. The firing time is long (1-1.5h), the production cost is high, and the acid and alkali resistance of the brick surface is not involved.

[0004] In summary, the purpose of this application is to provide a preparation method and application of acid- and alkali-resistant high-transmittance black brick glaze, which can ensure that the glaze surface of black bricks and conventional light-colored production plates has a strong sense of transparency, and the acid and alkali resistance is not lower than the GLB level, while taking into account the stability of the brick shape produced in the wide-body kiln and the matching of the firing temperature curve. Summary of the invention

[0005] In view of the above shortcomings, the present invention provides a method for preparing acid-alkali resistant and highly transparent black brick glaze and its application, which solves the problems of many pores on the glaze surface, poor transparency, poor acid-alkali resistance, and high firing temperature in the current preparation of black bricks. The specific technical scheme is as follows:

[0006] A black brick polishing glaze with acid and alkali resistance and high transparency comprises the following raw materials in parts by weight: 30-40 parts of potassium feldspar, 3-5 parts of zinc oxide, 5-9 parts of calcined talc, 4-7 parts of wollastonite, 2-6 parts of calcite, 6-9 parts of washed soil, 6-10 parts of barium sulfate, 7-10 parts of strontium sulfate, 7-9 parts of quartz and 6-8 parts of diopside.

[0007] Furthermore, an acid- and alkali-resistant high-transparency black brick glaze comprises the following raw materials in parts by weight: 30-34 parts of potassium feldspar, 4-5 parts of zinc oxide, 6-8 parts of calcined talc, 5-6 parts of wollastonite, 5-6 parts of calcite, 7-9 parts of washed soil, 7-10 parts of barium sulfate, 8-10 parts of strontium sulfate, 8-9 parts of quartz and 7-8 parts of diopside.

[0008] Furthermore, a kind of acid and alkali resistant high-transmittance black brick glaze is provided, and the raw materials of the acid and alkali resistant high-transmittance black brick glaze include the following chemical components by weight percentage: SiO2: 48%-52%, Al2O3: 8%-11%, BaO: 3%-5%, ZnO: 3%-5%, Na2O: 1%-2%, MgO: 2%-5%, K2O: 2%-4%, CaO: 8%-10%, SrO: 3%-5%, SO3: 4%-5% and LOI: 4%-7.5%.

[0009] The present invention also provides an acid-alkali resistant and highly transparent black brick, wherein the black brick is prepared by using the above-mentioned polished glaze.

[0010] Furthermore, the method for preparing the black brick comprises the following steps:

[0011] (1) Making glaze: after uniformly mixing the raw materials of glaze according to the proportion, put them into a ball mill, add water, carboxymethyl cellulose and sodium tripolyphosphate and grind them together, 0.30-0.45wt% residue is left after passing through a 325-mesh sieve, and age for 17-21h to obtain glaze;

[0012] The raw materials of the glaze include the following chemical components by weight percentage: SiO2: 50%-52%, Al2O3: 32%-35%, CaO: 1%-2%, K2O: 1%-2%, ZrO2: 4%-6%, MgO: 1%-1.5%, BaO: 2%-5%, Na2O: 3%-5% and LOI: 1%-1.5%;

[0013] (2) Applying glaze: pouring the glaze on the brick, the specific gravity of the glaze is controlled at 1.86-1.88, the flow rate is controlled at 26-32s, and the pouring amount is 490-510g / m 2 ;

[0014] (3) Making polishing glaze: after uniformly mixing the raw materials of the polishing glaze according to the proportion, the raw materials are put into a ball mill, and water, carboxymethyl cellulose and sodium tripolyphosphate are added and ball-milled together, and the residue after passing through a 325-mesh sieve is 0.30-0.45 wt %, and the polishing glaze is aged for 17-21 hours to obtain the polishing glaze;

[0015] (4) Applying glaze: The glaze is evenly poured on the brick blank with the surface glaze to obtain the brick blank to be fired; the specific gravity of the glaze is controlled at 1.86-1.90, the flow rate is controlled at 26-32s, and the glaze pouring amount is 500-520g / m 2 ;

[0016] (5) Low-temperature fast firing: The brick to be fired is fired at 1140-1160° C. for 40-46 min to obtain the black brick.

[0017] Furthermore, in step (1), the glaze is prepared by uniformly mixing the glaze raw materials according to a ratio, putting the mixture into a ball mill, adding 40% water, 0.17% carboxymethyl cellulose and 0.32% sodium tripolyphosphate, and ball milling the mixture together.

[0018] Furthermore, in step (2), step (2) and step (4), the method of applying the surface glaze and the method of applying the polishing glaze are both to use a bell jar to evenly pour the glaze on the surface of the brick.

[0019] Furthermore, in step (3), the glaze is prepared by uniformly mixing the glaze raw materials according to a ratio, putting them into a ball mill, adding 36% water, 0.16% carboxymethyl cellulose and 0.3% sodium tripolyphosphate, and ball milling them together.

[0020] Furthermore, in step (5), the low-temperature fast firing is to fire the brick to be fired at 1145-1150° C. for 43-45 minutes.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention adjusts the glaze formula, matches the existing production glaze, and coordinates the formula component system to take into account all aspects of the glaze performance. On the premise of ensuring that the glaze of black bricks and conventional light-colored production plates has a strong sense of transparency and acid and alkali resistance is not lower than GLB level, it also takes into account the stability of the brick shape produced by the wide-body kiln and the matching of the firing temperature curve.

[0023] 2. When quartz comes into contact with alkaline substances, only soluble silicates are generated, which have strong acid corrosion resistance, while SiO2 can form a stable silicate structure, and its chemical properties are inert and stable. The present invention utilizes the characteristics of quartz and SiO2 to increase the quartz content and SiO2 content in the glaze, thereby improving the acid and alkali resistance of the glaze and making the acid and alkali resistance of the glaze and the brick surface not lower than the GLB level.

[0024] 3. The present invention uses a Ba-Sr system glaze formula and utilizes the strong fluxing property of BaO to reduce the melting temperature and viscosity of the glaze, thereby improving the fluidity and glossiness of the glaze, enhancing the transparency and stability of the polished glaze, and at the same time appropriately increasing the calcite content in the formula to further enhance the transparency of the glaze surface, so that the transparency can take into account both dark layouts and conventional product production.

[0025] 4. The present invention increases the ZnO content in the formula, which can increase the fluidity of the glaze surface, improve the air exhaust, and further reduce the bubbles in the glaze layer and improve the pores of the glaze surface.

[0026] 5. The present invention introduces diopside into the glaze, which can increase the content of MgO and CaO in the glaze. MgO and CaO form a liquid phase at a relatively low temperature, which reduces the firing temperature and can avoid the increase of pores caused by a high SiO2 content. Therefore, the introduction of diopside can take into account both acid and alkali resistance and pore reduction, and can match it with the production firing temperature, widen the melting range, and is suitable for a low-temperature fast-firing environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for describing the embodiments are briefly introduced below.

[0028] Figure 1 This is a diagram of the pores on the surface of the black brick obtained in Example 1;

[0029] Figure 2 This is a diagram of the pores on the surface of the black brick obtained in Example 2;

[0030] Figure 3 This is a diagram of the pores on the surface of the black brick obtained in Example 3;

[0031] Figure 4 This is a diagram of the pores on the surface of the black brick obtained in Comparative Example 1;

[0032] Figure 5 This is a diagram of the pores on the surface of the black brick obtained in Comparative Example 2;

[0033] Figure 6 This is a diagram of the pores on the surface of the black brick prepared in Comparative Example 3. DETAILED DESCRIPTION

[0034] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.

[0035] Example 1

[0036] Glaze raw materials: 30 parts of potassium feldspar, 5 parts of zinc oxide, 7 parts of calcined talc, 6 parts of wollastonite, 6 parts of calcite, 9 parts of washed soil, 10 parts of barium sulfate, 10 parts of strontium sulfate, 9 parts of quartz and 8 parts of diopside.

[0037] Chemical composition of the glaze: SiO2: 51.7%, Al2O3: 9.85%, BaO: 4.43%, ZnO: 3.77%, Na2O: 1.18%, MgO: 3.75%, K2O: 2.96%, CaO: 8.74%, SrO: 3.48%, SO3: 4.37% and LOI: 5.77.

[0038] Chemical composition of the glaze: SiO2: 51%, Al2O3: 31.5%, CaO: 1.6%, K2O: 1.4%, ZrO2: 5%, MgO: 1.2%, BaO: 3.5%, Na2O: 3.3%, and the rest is lost due to burning.

[0039] The preparation method of acid and alkali resistant high-transmittance black brick is:

[0040] (1) Preparation of glaze: After the raw materials of the glaze are uniformly mixed according to the proportion, 40% water, 0.17% carboxymethyl cellulose and 0.32% sodium tripolyphosphate are added to a ball mill and ball-milled together, 0.40wt% of the residue is sieved through a 325-mesh sieve, and aged for 20 hours to obtain the glaze;

[0041] (2) Applying glaze: The glaze is evenly poured on the brick blank using a bell jar. The specific gravity of the glaze is controlled at 1.87, the flow rate is controlled at 31s, and the glaze pouring amount is 500g / m 2 ;

[0042] (3) Preparation of polishing glaze: After the raw materials of the polishing glaze are uniformly mixed according to the proportion, 36% water, 0.16% carboxymethyl cellulose and 0.3% sodium tripolyphosphate are added to a ball mill and ball-milled together, 0.40wt% of the residue is sieved through a 325-mesh sieve, and aged for 20 hours to obtain the polishing glaze;

[0043] (4) Applying glaze: The glaze is evenly poured onto the brick blank with the surface glaze by using a bell jar to obtain a brick blank to be fired; the glaze specific gravity is controlled at 1.88, the flow rate is controlled at 30s, and the glaze pouring amount is 510g / m 2 ;

[0044] (5) Low-temperature fast firing: The brick to be fired is fired at 1149°C for 44 minutes to obtain a black brick.

[0045] Example 2

[0046] Glaze raw materials: 36 parts of potassium feldspar, 5 parts of zinc oxide, 5 parts of calcined talc, 6 parts of wollastonite, 4 parts of calcite, 9 parts of washed soil, 10 parts of barium sulfate, 10 parts of strontium sulfate, 7 parts of quartz and 8 parts of diopside.

[0047] Chemical composition of the polishing glaze: SiO2: 49.92%, Al2O3: 9.92%, BaO: 4.41%, ZnO: 3.72%, Na2O: 1.52%, MgO: 3.52%, K2O: 4.56%, CaO: 7.52%, SrO: 3.42%, SO3: 4.32% and LOI: 7.17.

[0048] Chemical composition of the glaze: SiO2: 51%, Al2O3: 31.5%, CaO: 1.6%, K2O: 1.4%, ZrO2: 5%, MgO: 1.2%, BaO: 3.5%, Na2O: 3.3%, and the rest is lost due to burning.

[0049] The preparation method of acid and alkali resistant high-transmittance black brick is:

[0050] (1) Preparation of glaze: After the raw materials of the glaze are uniformly mixed according to the proportion, 40% water, 0.17% carboxymethyl cellulose and 0.32% sodium tripolyphosphate are added to a ball mill and ball-milled together, 0.30wt% of the residue is sieved through a 325-mesh sieve, and aged for 17 hours to obtain the glaze;

[0051] (2) Applying glaze: The glaze is evenly poured on the brick blank using a bell jar. The specific gravity of the glaze is controlled at 1.86, the flow rate is controlled at 32s, and the glaze pouring amount is 490g / m 2 ;

[0052] (3) Preparation of polishing glaze: After the raw materials of the polishing glaze are uniformly mixed according to the proportion, 36% water, 0.16% carboxymethyl cellulose and 0.3% sodium tripolyphosphate are added to a ball mill and ball-milled together, 0.30wt% of the residue is sieved through a 325-mesh sieve, and aged for 17 hours to obtain the polishing glaze;

[0053] (4) Applying glaze: The glaze is evenly poured onto the brick blank with the surface glaze by using a bell jar to obtain a brick blank to be fired; the glaze specific gravity is controlled at 1.86, the flow rate is controlled at 32s, and the glaze pouring amount is 500g / m 2 ;

[0054] (5) Low-temperature fast firing: The brick to be fired is fired at 1140° C. for 46 min to obtain the black brick.

[0055] Example 3

[0056] Glaze raw materials: 40 parts of potassium feldspar, 3 parts of zinc oxide, 9 parts of calcined talc, 6 parts of wollastonite, 2 parts of calcite, 6 parts of washed soil, 10 parts of barium sulfate, 7 parts of strontium sulfate, 9 parts of quartz and 8 parts of diopside.

[0057] Chemical composition of the polishing glaze: SiO2: 51.2%, Al2O3: 9.5%, BaO: 4.44%, ZnO: 2.78%, Na2O: 2.38%, MgO: 3.98%, K2O: 8.53%, CaO: 6.12%, SrO: 2.11%, SO3: 4.34% and LOI: 4.62.

[0058] Chemical composition of the glaze: SiO2: 51%, Al2O3: 31.5%, CaO: 1.6%, K2O: 1.4%, ZrO2: 5%, MgO: 1.2%, BaO: 3.5%, Na2O: 3.3%, and the rest is lost due to burning.

[0059] The preparation method of acid and alkali resistant high-transmittance black brick is:

[0060] (1) Preparation of glaze: After the raw materials of the glaze are uniformly mixed according to the proportion, 40% water, 0.17% carboxymethyl cellulose and 0.32% sodium tripolyphosphate are added to a ball mill and ball-milled together, 0.0.45wt% of the residue is sieved through a 325-mesh sieve, and aged for 21 hours to obtain the glaze;

[0061] (2) Applying glaze: The glaze is evenly poured on the brick blank using a bell jar. The specific gravity of the glaze is controlled at 1.88, the flow rate is controlled at 26s, and the glaze pouring amount is 490g / m 2 ;

[0062] (3) Preparation of polishing glaze: After the raw materials of the polishing glaze are uniformly mixed according to the proportion, 36% water, 0.16% carboxymethyl cellulose and 0.3% sodium tripolyphosphate are added to a ball mill and ball-milled together, 0.45wt% of the residue is sieved through a 325-mesh sieve, and aged for 21 hours to obtain the polishing glaze;

[0063] (4) Applying glaze: The glaze is evenly poured onto the brick blank with the surface glaze by using a bell jar to obtain a brick blank to be fired; the glaze specific gravity is controlled at 1.90, the flow rate is controlled at 26s, and the glaze pouring amount is 500g / m 2 ;

[0064] (5) Low-temperature fast firing: The brick to be fired is fired at 1160° C. for 40 min to obtain the black brick.

[0065] Comparative Example 1

[0066] The specific components of the glaze are as follows by weight: 30 parts of potassium feldspar, 5 parts of zinc oxide, 7 parts of calcined talc, 6 parts of wollastonite, 6 parts of calcite, 11 parts of washed soil, 10 parts of barium sulfate, 10 parts of strontium sulfate, 11 parts of quartz and 4 parts of diopside.

[0067] The chemical composition range of the glaze is: SiO2: 52.12%, Al2O3: 9.98%, BaO: 4.43%, ZnO: 3.75%, Na2O: 1.32%, MgO: 3.72%, K2O: 2.99%, CaO: 7.12%, SrO: 3.48%, SO3: 4.37% and LOI: 6.72.

[0068] The chemical composition of the glaze is the same as that of Example 1; the preparation method of the black brick is the same as that of Example 1.

[0069] Comparative Example 2

[0070] The specific components of the glaze are as follows by weight: 36 parts of potassium feldspar, 5 parts of zinc oxide, 5 parts of calcined talc, 8 parts of wollastonite, 6 parts of calcite, 9 parts of washed soil, 10 parts of barium sulfate, 10 parts of strontium sulfate and 11 parts of quartz.

[0071] The chemical composition range of the glaze is: SiO2 51.81%, Al2O3 9.85%, BaO 4.43%, ZnO 3.77%, Na2O1.18%, MgO 3.51%, K2O 4.58%, CaO 8.75%, SrO 3.46%, SO3 4.39% and LOI: 4.63.

[0072] The chemical composition of the glaze is the same as that of Example 1; the preparation method of the black brick is the same as that of Example 1.

[0073] Comparative Example 3

[0074] The specific components of the glaze are as follows by weight: 36 parts of potassium feldspar, 3 parts of zinc oxide, 5 parts of calcined talc, 6 parts of wollastonite, 4 parts of calcite, 11 parts of washed soil, 10 parts of barium carbonate, 10 parts of strontium sulfate, 9 parts of quartz and 8 parts of diopside.

[0075] The chemical composition range of the glaze is: SiO2 51.92%, Al2O3 9.87%, BaO 4.48%, ZnO 3.79%, Na2O1.21%, MgO 3.68%, K2O 4.56%, CaO 8.95%, SrO 3.46%, SO3 2.98% and LOI:5.10.

[0076] The chemical composition of the glaze is the same as that of Example 1; the preparation method of the black brick is the same as that of Example 1.

[0077] The glaze raw material components of each embodiment and comparative example are shown in Table 1:

[0078] Table 1 Glaze raw material components

[0079]

[0080]

[0081] The performance of the black bricks prepared in each embodiment and comparative example was tested according to GB / T 3810.14-2016 standard. The results are shown in Table 2:

[0082] Table 2 Transparency, pores and corrosion resistance of black bricks in various embodiments and comparative examples

[0083] Project / Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Transparent good good better better better generally Pore ​​condition after polishing none few few More many many 3% hydrochloric acid solution GLA GLA GLA GLA GLA GLA 30g / L potassium hydroxide solution GLA GLB GLA GLA GLB GLB 18% hydrochloric acid solution GLB GLB GLB GLB GLB GLB 100g / L potassium hydroxide solution GLA GLA GLA GLB GLA GLB 100g / L ammonium chloride solution GLA GLA GLA GLA GLA GLA 200g / L sodium hypochlorite solution GLA GLA GLA GLA GLA GLA 100g / L citric acid solution GLA GLB GLA GLA GLA GLA

[0084] It can be seen from the data of Example 2, Example 3 and Example 1 in the table that with the increase of SiO2 content, the acid and alkali resistance of the brick surface gradually increases, but the pores also gradually increase. This is because the increase of SiO2 content in the polishing glaze can significantly improve the chemical stability and thermal stability of the glaze, which helps to reduce the uneven stress distribution in the glaze layer, thereby improving the acid and alkali resistance. However, when the SiO2 content is too high, the firing temperature is too high, and the gas in the blank and glaze cannot be completely and smoothly discharged, resulting in more pores after polishing. With the increase of calcite, the glaze surface transparency also increases, which is mainly because the appropriate increase of calcite (CaCO3) in this formula can increase the refractive index of the glaze, thereby improving the glossiness and improving the light transmittance of the glaze. With the increase of ZnO content, the pores also become better, because ZnO can increase the fluidity of the glaze, improve exhaust, reduce bubbles in the glaze layer, and improve the pores of the glaze.

[0085] It can be seen from Comparative Example 1, Comparative Example 2 and Example 1 that with the increase in the amount of diopside added, the pores on the brick surface gradually improve. This is because with the increase of diopside, the content of MgO and CaO in the glaze also increases. MgO and CaO form a liquid phase at a lower temperature, which can reduce the firing temperature and avoid the increase of pores when the SiO2 content is high, so that it matches the production firing temperature.

[0086] It can be seen from Comparative Example 3 and Example 1 that barium carbonate and barium sulfate both have good transparency for black bricks, but barium carbonate has a greater impact on the glaze pores. This is because barium carbonate decomposes CO2 at high temperatures, increasing the generation of bubbles in the glaze, thereby affecting the pores on the brick surface.

[0087] In summary, the present invention adjusts the glaze formula, matches the existing production glaze, coordinates the formula component system to take into account all aspects of the glaze performance, and takes into account the stability of the brick shape produced by the wide-body kiln and the matching of the firing temperature curve while ensuring that the glaze of black bricks and conventional light-colored production plates has a strong sense of transparency and acid and alkali resistance is not lower than GLB level.

[0088] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.

Claims

1. A kind of acid and alkali resistant high-transparency black brick glaze, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of potassium feldspar, 3-5 parts of zinc oxide, 5-9 parts of calcined talc, 4-7 parts of wollastonite, 2-6 parts of calcite, 6-9 parts of washed soil, 6-10 parts of barium sulfate, 7-10 parts of strontium sulfate, 7-9 parts of quartz and 6-8 parts of diopside.

2. The acid-base resistant and highly transparent black brick glaze according to claim 1 is characterized in that: The invention comprises the following raw materials in parts by weight: 30-34 parts of potassium feldspar, 4-5 parts of zinc oxide, 6-8 parts of calcined talc, 5-6 parts of wollastonite, 5-6 parts of calcite, 7-9 parts of washed soil, 7-10 parts of barium sulfate, 8-10 parts of strontium sulfate, 8-9 parts of quartz and 7-8 parts of diopside.

3. The acid-base resistant and highly transparent black brick glaze according to claim 1 or 2, characterized in that: The acid-alkali resistant and high-transmittance black brick glaze raw materials include the following chemical components by weight percentage: SiO2: 48%-52%, Al2O3: 8%-11%, BaO: 3%-5%, ZnO: 3%-5%, Na2O: 1%-2%, MgO: 2%-5%, K2O: 2%-4%, CaO: 8%-10%, SrO: 3%-5%, SO3: 4%-5% and LOI: 4%-7.5%.

4. A black brick with high acid and alkali resistance, characterized in that: The black brick is prepared by using the glaze polishing method as described in any one of claims 1 to 3.

5. The acid-alkali resistant and highly transparent black brick according to claim 4, characterized in that: The method for preparing the black brick comprises the following steps: (1) Making glaze: after uniformly mixing the raw materials of glaze according to the proportion, put them into a ball mill, add water, carboxymethyl cellulose and sodium tripolyphosphate and grind them together, 0.30-0.45wt% residue is left after passing through a 325-mesh sieve, and age for 17-21h to obtain glaze; The raw materials of the glaze include the following chemical components by weight percentage: SiO2: 50%-52%, Al2O3: 32%-35%, CaO: 1%-2%, K2O: 1%-2%, ZrO2: 4%-6%, MgO: 1%-1.5%, BaO: 2%-5% and Na2O: 3%-5%; (2) Applying glaze: pouring the glaze on the brick, the specific gravity of the glaze is controlled at 1.86-1.88, the flow rate is controlled at 26-32s, and the pouring amount is 490-510g / m 2 ; (3) Making polishing glaze: after uniformly mixing the raw materials of the polishing glaze according to the proportion, the raw materials are put into a ball mill, and water, carboxymethyl cellulose and sodium tripolyphosphate are added and ball-milled together, and the residue after passing through a 325-mesh sieve is 0.30-0.45 wt %, and the polishing glaze is aged for 17-21 hours to obtain the polishing glaze; (4) Applying glaze: The glaze is evenly poured on the brick blank with the surface glaze to obtain the brick blank to be fired; the specific gravity of the glaze is controlled at 1.86-1.90, the flow rate is controlled at 26-32s, and the glaze pouring amount is 500-520g / m 2 ; (5) Low-temperature fast firing: The brick to be fired is fired at 1140-1160° C. for 40-46 min to obtain the black brick.

6. The acid-alkali resistant and highly transparent black brick according to claim 5, characterized in that: In step (1), the glaze is prepared by uniformly mixing the raw materials of the glaze according to the proportion, putting them into a ball mill, adding 40% water, 0.17% carboxymethyl cellulose and 0.32% sodium tripolyphosphate, and ball milling them together.

7. The acid-alkali resistant and highly transparent black brick according to claim 5, characterized in that: In step (2) and step (4), the method of applying the surface glaze and the method of applying the polishing glaze are both to use a bell jar to evenly pour the glaze on the surface of the brick.

8. The acid-alkali resistant and highly transparent black brick according to claim 5, characterized in that: In step (3), the glaze is prepared by uniformly mixing the glaze raw materials according to the proportion, putting them into a ball mill, adding 36% water, 0.16% carboxymethyl cellulose and 0.3% sodium tripolyphosphate, and ball milling together.

9. The acid-alkali resistant and highly transparent black brick according to claim 5, characterized in that: In step (5), the low temperature fast firing is to fire the brick to be fired at 1145-1150°C for 43-45 minutes.

Citation Information

Patent Citations

  • Acid and alkali resistant fully polished glazed ceramic tile and its preparation method

    CN108975704B

  • Production method of portoro glaze ceramic

    CN109231824A

  • Lava black brick glaze as well as preparation method and application thereof

    CN113213764A

  • Black golden flower ceramic tile surface treatment glaze and method

    CN115849712A

  • Wear-resistant full-raw material super-flat thick polishing glaze and application thereof

    CN106542735A